Psychopathy from a Basic Trait Perspective: The Utility of a Five‐Factor Model Approach. Issue 6 (10th November 2014) - Lynam, Donald R.; Miller, Joshua D.
Abstract: The present article argues that psychopathy is best understood as a collection of traits from the Five‐Factor Model of personality (FFM). We demonstrate that specific FFM traits involved in psychopathy are well delineated; the same personality profile emerges across methods. We review research demonstrating that this FFM profile can be used to assess psychopathy, including the development of a psychopathy‐specific FFM assessment that appears to do an even better job of assessing psychopathy than the NEO PI‐R while remaining true to the basic structural model. We demonstrate the advantages to understanding psychopathy in this way. The FFM provides an assay of extant inventories, accounts for the epidemiology of psychopathy, and explains the factor structure of various inventories. The elemental view of psychopathy allows psychopathy to be built from the ground up, trait by trait. Perhaps most importantly, the FFM is unique in providing a connection to basic research in personality.